Provinha Brasil: a utilização e avaliação dos testes de diagnósticos da alfabetização pelos professores - Marinilda Maia (2010)
The researchs purpose is to study the current political actions of external evaluation of public schools, by analyzing the application of Provinha Brasil, whose objective is to help teachers to diagnose the initial acquisitions on the literacy process of students from the initial years of basic education. The use of those evaluative devices is proposed by teachers to define goals and teaching and learning activities for the annual pedagogical planning. To develop that research, were carried out semi-structured interviews with literacy teachers from two public schools of the city of Belo Horizonte, in order to investigate what kind relationships teachers establish with the propose of diagnostic evaluation of Provinha Brasil, applied in year 2009 and in which way that device have contributed to the pedagogical work on the schools. The study showed that, first, due to the current monitoring of the school practices, through a systematic application of large scale evaluations, it becomes difficult for teachers to distinguish between the different aims of the evaluations the schools have systematically been through. Secondly, the study revealed that teachers, when using in differentiated ways the tests and results of the Provinha, begin to analyze the limits and the pedagogical possibilities of that device.